2018
DOI: 10.1136/bjsports-2018-099131
|View full text |Cite
|
Sign up to set email alerts
|

Is the time right for quantitative public health guidelines on sitting? A narrative review of sedentary behaviour research paradigms and findings

Abstract: Sedentary behaviour (SB) has been proposed as an 'independent' risk factor for chronic disease risk, attracting much research and media attention. Many countries have included generic, non-quantitative reductions in SB in their public health guidelines and calls for quantitative SB targets are increasing. The aim of this narrative review is to critically evaluate key evidence areas relating to the development of guidance on sitting for adults. We carried out a non-systematic narrative evidence synthesis across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
209
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(219 citation statements)
references
References 97 publications
(111 reference statements)
6
209
0
4
Order By: Relevance
“…Nowadays, studies investigating SB use small and lightweight body‐worn sensors capable to record free‐living behavior over several days . However, the device‐based SB measure is not consistent with its definition, and research is far away to stipulate evidence‐based health recommendations …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, studies investigating SB use small and lightweight body‐worn sensors capable to record free‐living behavior over several days . However, the device‐based SB measure is not consistent with its definition, and research is far away to stipulate evidence‐based health recommendations …”
Section: Introductionmentioning
confidence: 99%
“…7 However, the device-based SB measure is not consistent with its definition, 8,9 and research is far away to stipulate evidence-based health recommendations. 10 Probably the most frequently used sensor to measure SB is the ActiGraph (ActiGraph LCC, Pensacola, USA). The ActiGraph with its proprietary counts per minute (cpm) was originally developed to measure physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, subjective assessments of sedentary behavior in one domain may not be a valid measure of the total amount of daytime SED [43]. SED has been shown to be a risk factor for metabolic health, that is partly independent of aerobic fitness and MVPA [32] (but see also [44,45]). It would therefore be expected that higher %SED would be associated with worse rather than better cognitive functions, especially among low fit individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Within epidemiological studies, the associations 46 between television time and cardiometabolic health outcomes are generally interpreted to be 47 effects of sitting. However, the association between TV time and poor health outcomes is 48 stronger than the association between total sitting time 1-3 or time spent sitting in other 49 confounding effects by socioeconomic position 5 , or factors such as snacking 1 , have been put 52 forward as potential explanations, the type of sitting associated with TV time may play an 53 important role. For example, based on experimental evidence showing that breaking up 54 sitting is associated with lower glucose and insulin levels compared to uninterrupted bouts of 55 sitting 6 , it has been suggested that watching TV might be associated with prolonged ST, and 56 be detrimental for that reason 1,2,7 .…”
Section: Introduction 44mentioning
confidence: 99%